Brand Influence in Business-to-Business (B2B) Markets : Understanding the Buying Criteria of Different Organizations - Raychaudhuri, P. S.; Garg, Aman (Indian Journal of Marketing, 2016)
The brands make identification of products, services, and businesses convenient, easy, and more acceptable for the buyers. Besides, the brands help to differentiate them from competitors’ offerings. The brands also communicate improved value and benefits to the business buyers. And brands also act as a measure of guarantee for quality, performance, and the source; and thus reduce the risk and complexities in buying decisions. The objective of the study was to have a deeper understanding of the various evaluative criteria used in different B2B purchase decisions, and to what extent a brand influences them and how beneficial are those decisions for the buying organizations. The study was focused around the value and importance of branding, the preference towards branded products, and the effect of factors like price, risks involved, information availability, customer support/ after sales services, and value addition on purchase decisions in organizations. The study was conducted with 110 respondents from four different industry categories purchasing and using namely, garment manufacturing machinery, photocopiers,Â photographic equipment, and medical diagnostic equipments with the help of a questionnaire and interview. The study revealed that more or less, industrial and organizational buyers, though very price conscious, prefer branded products because it gives a mental satisfaction that they are buying a quality product and associated services from a reliable and known source. The companies supplying branded products provide quick backup service and support, and they are more preferred because it assures quick response and solution of any bottleneck and issue with the final end product/ service produced in the buying organization.